The Future of Russian-Japanese Relations in Light of the Crisis in the Kuril Islands - Hamzah, Majeed Kamil; Esmael, Ahmed Abid; Abbas, Faisal Shallal (Utopía y Praxis Latinoamericana, 2020)
ABSTRACTRelations between Russia and Japan follow two unequal tracks, a network of cooperation slowly expanding in various fields, and a territorial dispute over the Kuril Islands. In 1956, Japan and the Soviet Union signed the ceasefire agreement. Japan binds the conclusion of the peace treaty between the two countries, with the return of Russia to the four Kuril Islands that the Soviet Union annexed to its lands in the framework of the results of the Second World War, while Russia is adhering to its right to own